If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -4 = 8(x + -9) Reorder the terms: -4 + 8x = 8(x + -9) Reorder the terms: -4 + 8x = 8(-9 + x) -4 + 8x = (-9 * 8 + x * 8) -4 + 8x = (-72 + 8x) Add '-8x' to each side of the equation. -4 + 8x + -8x = -72 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 + 0 = -72 + 8x + -8x -4 = -72 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 = -72 + 0 -4 = -72 Solving -4 = -72 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 25a+50b=600 | | 2(x^(1/2))*(10^(1/2)-1)=9 | | 8x+6z=2+3y | | 7/4=6/x-2 | | 4x-9y=14 | | y=x^2+24x+29 | | 2(8x-6)=4(4x-3) | | -3(x+6)+2=-16 | | -6x^2+6x+17=0 | | b=47+27 | | 6x^2-6x+17=0 | | 2x=180+10-90 | | 52-2=c | | 3x-26+x=180 | | 2x-2=8+x | | 6x+4z=7+5y | | h(x+4)=x+x*2 | | x(x-2)+(1-3y)(1+3y)= | | (5a)(-8ab)(2a)= | | 9y-3(6-5)=y-2(3y+9) | | 2e+e= | | .5(4x+8)-16=-.67(9x-12) | | 3.2y+5=3(1.4y+4) | | e(3x-4)e(-x)=3e | | 6(4)6-3x=384 | | 15y-6y(4t+8t)= | | Cos(2x)+cosx=0 | | 8x+8=32+8 | | 5-(x+3)=1+2(x-3) | | 2m^2+m+9=0 | | (5a)*(-8ab)*(2a)= | | 100=2(x+11)(x-5)-x(x+11) |